Acute Deep Vein Thrombosis Treated with Porcine Plasmin - Storm, O; Ollendorff, P; Drewsen, E; Tang, P (Thrombosis and Haemostasis, 1974)
The thrombolytic effect of pig plasmin was tested in a double blind trial on patients with deep venous thrombosis in the lower limb. Only patients with not more than three days old thrombi were selected for this study. The diagnosis of deep vein thrombosis was made clinically and confirmed by phlebography. Lysofibrin Novo (porcine plasmin) or placebo (porcine plasminogen) was administered intravenously to the patients. The enzyme and the placebo were delivered as lyophilized powder in labelled bottles - the contents of the bottles were unknown to the doctor in charge of the clinical administration of the trial. An initial dose of plasmin/plasminogen of 30 unit per kg body weight given slowly intravenously (1-1% hours infusion) was followed by a maintenance dosis of 15 per cent the initial dose per hour for the following 5-7 hours. In most cases a similar maintenance dosis was given the next day. In all patients heparin was administered after ending the plasmin/plasminogen infusion. The results of the treatment was evaluated clinically as well as by control phlebo- grams the following days.A statistically significant improvement was found in the plasmin treated group compared with the placebo (plasminogen) treated group. Thrombolysis was obtained clinically and phlebographically in 65 per cent of the plasmin treated group, but only in 15 per cent of the control patients were improvements found.This study has thus demonstrated that plasmin treatment according to a standard scheme was able to induce thrombolysis. There were only a few and insignificant side effects. Allergic reactions have not been seen and only very simple tests are required.